PENINGKATAN KEUNGGULAN BERSAING BERBASIS KNOWLEDGE MANAGEMENT MELALUI INTELLECTUAL CAPITAL DAN INOVASI DI SURABAYA PLAZA HOTEL - Purnamawati .; Yusak Anshori (Journal of Business & Banking, 2013)
In connection with the development of tourism in East Java from 2009 to 2011, it has shown that this sector has been indicated as having good prospect and progress. The purpose of this study was to analyze competitive advantage based on Knowledge Management (KM) through Intellectual Capital (IC) and Innovation at Surabaya Plaza Hotel. This study is a qualitative research using a case study approach. In collecting the data, an interview was done to the General Manager, the Resident Manager, eight Department Heads, the employees of the Month (EOM), the employees of the Year (EOY), and the supervisor of the Quarter (SOQ). Besides an interview, this study also conducted an observation. In addition, the reliability of this research was conducted by using triangulation technique. The results show that intangible asset is considered more important than tangible asset in the hotel and that it is probably important to evaluate IC, Innovation as well as KM with business performance. The synergy of KM, IC and Innovation aligned with business strategy has produced a competitive advantage.